The role of Saudi women in economic and social development in light of the Kingdom's Vision 2030 : An analytical study - Mohamed, Amel ElMahi ElKhlifa (Journal of Humanities & Social Sciences, 2020)
This study aims at highlighting the role of Saudi women in the development of their society, by achieving the objectives of economic and social development in line with their relative weight in society, and the rapid development in their expertise, scientific and practical capabilities in accordance with the vision of the Kingdom of 2030.An analytical method has been adopted to analyze the actuality of Saudi women number in 2017. The study found that Saudi women are continuously supported and empowered, increasing the rate of qualifying and training women, and integrating them into development plans as stated in the Kingdom's Vision 2030, the percentage of their employees in the private sector increased to 10% and the unemployment rate to be reduced from 12.3% to 9% in By 2020. Therefore, the study recommends more attention to Saudi women and give them the right of employment and work.
Keywords: Saudi women; economic development; social development; Vision 2030